PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN TRANSAKSIONAL TERHADAP IKLIM ORGANISASI DAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR - Moh. In’am Latif (Jurnal Bisnis dan Manajemen, 2018)
The purpose of this study aims to analyzes how much influence transformational leadership (X1) and transactional leadership (X2) to organizational climate (Z) and organizational citizenship behavior (Y) at RSUD Genteng Kabupaten Banyuwangi. This research used a quantitative approach with Partial Least Square. As for the number of samples as many 130 respondents taken by using Proportional Random Sampling method. The results of this study whole that transformational leadership and transactional leadership have a significant effect on organizational climate. Transformational leadership and transactional leadership have a significant effect on organizational citizenship behavior, either directly or indirectly through organizational climate. Based on the results of this study, the management of hospitals need to develop what has been a common perception and understanding between the leadership with employees, by innovating in terms of policy leaders, both for the organization as a whole or required for employees. DOI : https://doi.org/10.26905/jbm.v5i1.2316